2020
DOI: 10.2486/indhealth.2018-0264
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of problem gambling in an employed population in Brittany, France

Abstract: Some employees may have recourse to gambling, notably as an adaptive strategy. Although many studies have been performed on specific occupational groups (i.e. gambling industry, transportation or teaching), none have been conducted with workers followed-up by Occupational Health Services (OHS). Our aim was to evaluate the prevalence of problem gambling in an employed population and its links with work. We performed a cross-sectional study between November 2016 and April 2017, in an OHS in France. We evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
1
Order By: Relevance
“…This could be explained by unemployed bettors who can turn to gamble because they are bored, have nothing else to do, and many hope that by gambling they can change their life (41). However, this nding is inconsistent with the study conducted in France which revealed that there was no signi cant association between unemployed and problematic gambling (42). This inconsistency might be explained by the difference in employed status and working time.…”
Section: Discussioncontrasting
confidence: 94%
“…This could be explained by unemployed bettors who can turn to gamble because they are bored, have nothing else to do, and many hope that by gambling they can change their life (41). However, this nding is inconsistent with the study conducted in France which revealed that there was no signi cant association between unemployed and problematic gambling (42). This inconsistency might be explained by the difference in employed status and working time.…”
Section: Discussioncontrasting
confidence: 94%